2021
DOI: 10.1038/s41388-021-01904-4
|View full text |Cite
|
Sign up to set email alerts
|

Context-dependent modulation of aggressiveness of pediatric tumors by individual oncogenic RAS isoforms

Abstract: A prototypic pediatric cancer that frequently shows activation of RAS signaling is embryonal rhabdomyosarcoma (ERMS). ERMS also show aberrant Hedgehog (HH)/GLI signaling activity and can be driven by germline mutations in this pathway. We show, that in ERMS cell lines derived from sporadic tumors i.e. from tumors not caused by an inherited genetic variant, HH/GLI signaling plays a subordinate role, because oncogenic mutations in HRAS, KRAS, or NRAS (collectively named oncRAS) inhibit the main HH target GLI1 vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…As described above, we recently generated Ptch +/mice that harbor a conditional oncogenic NRasG12D (NRas fl ) allele [12]. To activate the expression of oncNRAS in ERMS of Ptch +/-NRas fl/+ mice, the animals were bred to Myf5 CreER mice that express a tamoxifeninducible Cre recombinase in Myf5-expressing cells [12,13].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As described above, we recently generated Ptch +/mice that harbor a conditional oncogenic NRasG12D (NRas fl ) allele [12]. To activate the expression of oncNRAS in ERMS of Ptch +/-NRas fl/+ mice, the animals were bred to Myf5 CreER mice that express a tamoxifeninducible Cre recombinase in Myf5-expressing cells [12,13].…”
Section: Resultsmentioning
confidence: 99%
“…As described above, we recently generated Ptch +/mice that harbor a conditional oncogenic NRasG12D (NRas fl ) allele [12]. To activate the expression of oncNRAS in ERMS of Ptch +/-NRas fl/+ mice, the animals were bred to Myf5 CreER mice that express a tamoxifeninducible Cre recombinase in Myf5-expressing cells [12,13]. Using this model, we showed that induction of oncNRAS in 4-week-old Ptch +/mice does not influence incidence, growth or proliferation of the tumors when compared to the controls [12] (summarized in Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MEK or MAP2K) ( 48 52 ). Furthermore, oncogenic RAS can – dependent on the cancer entity – also inhibit GLI via MEK and/or ERK (extracellular signal-regulated kinase) ( 53 , 54 ). Additionally, WNT signaling is able to interfere with GLI signal transduction.…”
Section: The Hh Signaling Pathwaymentioning
confidence: 99%
“…Further, SHH seems to control self-renewal of FN-RMS; its inhibition has been shown to reduce chemotherapy resistance [69]. In addition, there is new evidence that oncogenic RAS mutations (HRAS, KRAS and NRAS) inhibit GLI1 via the MEK/ERK pathway but concurrently lead to increased proliferation and oncogenicity [70].…”
Section: Signaling Pathways In Rmsmentioning
confidence: 99%